Microbiome-Metabolome Responses in Ruminal Content and Feces of Lactating Dairy Cows With N-Carbamylglutamate Supplementation Under Heat Stress - Li, Yan; Ma, Ning; Ren, Liyuan; Wang, Meimei; Hu, Linqi; Shen, Yizhao; Cao, Yufeng; Li, Qiufeng; Li, Jianguo; Gao, Yanxia (Frontiers in Veterinary Science, 2022)
The objective of present study was to investigate the effects of N-carbamylglutamate (NCG) supplementation on metabolic profile and microbiota in rumen content and feces of lactating dairy cows under heat stress (HS). Forty-eight lactating Holstein cows (154 ± 13.6 days in milk) were assigned randomly into 4 treatments (n = 12), to receive 0, 15, 20 or 25 g/d of commercial NCG (proportion: 97.7%) for the period of 60 days. The recorded ambient temperature-humidity index (THI) suggested the cows were exposed to HS for almost the entire experimental period (average THI: 80.6). Samples of rumen content and feces were collected at the end of the trial (day 60) to determine the biological effects of NCG supplementation on metabolome and microbiota using mass spectrometry-based metabonomics and 16S rRNA gene sequencing techniques, respectively. Results showed that NCG supplementation enhanced the levels of ruminal microbial protein, acetate, propionate, butyrate and total volatile fatty acids (VFAs) in rumen, but lowered the ruminal pH, NH3-N and the ratio of acetate to propionate. NCG at doses of 20 and 25 g/d reduced the community richness and diversity of rumen microbiota with the decrease of Shannon and Simpson diversity. Compositions of ruminal and fecal microbiotas were altered by NCG, and the PICRUSt results revealed that metabolic pathways of the bacteria, such as amino acid metabolism, energy metabolism and pyruvate metabolism, were enriched in NCG groups. Distinct changes in metabonomic profile of rumen fluid were observed between control and NCG groups. Changes of twenty-six metabolites mainly involved in arginine metabolism, glutamate metabolism and nitrogen metabolism were observed in associated with NCG supplementation. These results provided new insights to the effects of NCG on metabolomic profile and microbiota in rumen content and feces, which contributed to understanding the effects of NCG on HS in lactating dairy cows.